Paediatric symptom and sign sorter - El-Radhi, A. Sahib (Boca Raton, FL : CRC Press, 2019)
This book will be a vital tool for all clinicians in the front line when an ill child presents with an acute illness. Experienced paediatricians, postgraduate doctors, primary care physicians, and paediatric nurses will find this a useful refresher, and it will be an invaluable primer for newly trained doctors and students, or those new to the paediatric wards. Each chapter here provides an overview of each symptom and sign followed by the most likely underlying causes in an easy-to-use tabular format. Investigative techniques and guidelines follow, ranging from the simple and inexpensive to the more complex, as do Top Tips and Red Flag warnings to note; new to this second edition are concluding summaries of Key Points, as well as an entirely new Endocrine chapter.
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Gynecology & Obstetrics; Symptoms in children -- Handbooks, manuals, etc; MEDICAL / General; MEDICAL / Family & General Practice; MEDICAL / Pediatrics